2011
DOI: 10.1158/1055-9965.epi-11-0668
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Squamous Cell Carcinoma of the Skin in Relation to IgE: a Nested Case–Control Study

Abstract: Background Individuals diagnosed with non-melanoma skin cancer have a high risk of developing a second skin cancer diagnosis. We assessed whether a marker of immune function related to atopic allergy, IgE, was associated with diagnosis of subsequent squamous cell carcinoma (SCC) of the skin in patients with a previous skin cancer enrolled in a skin cancer prevention trial. Methods One hundred twelve cases with a repeat skin cancer diagnosis were compared to 227 controls, matched on age, sex, and study center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Our trend towards an increased risk of SCC associated with allergy is consistent with the two previous studies examining SCC specifically (24, 32). For example, a longitudinal cohort study from Sweden, found a positive association with SCC and asthma (SIR 1.33, 95% CI 1.19-1.48) (24).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our trend towards an increased risk of SCC associated with allergy is consistent with the two previous studies examining SCC specifically (24, 32). For example, a longitudinal cohort study from Sweden, found a positive association with SCC and asthma (SIR 1.33, 95% CI 1.19-1.48) (24).…”
Section: Discussionsupporting
confidence: 92%
“…For example, a longitudinal cohort study from Sweden, found a positive association with SCC and asthma (SIR 1.33, 95% CI 1.19-1.48) (24). A more recent nested case-control study using IgE as a biological marker for atopic allergy observed an elevated risk of SCC in relation to higher IgE levels (32). Notably, the latter study had a high proportion of men, and in our study the positive association with SCC was largely confined to men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not statistically significant, patients who reported a history of any allergy showed an increased risk in SCC (OR 1.2, 95 % CI 0.8-1.8) and a decreased risk in BCC (OR 0.6, 95 % CI 0.4-1.0). In a nested case-control study conducted in the USA, IgE levels were higher in cases with SCC than controls (comparing those in the highest IgE level quartile to those in the lowest) [92]. However, there was no evidence of a dose-response trend, and the results were not statistically significant (OR 1.4, 95 % CI 0.7-2.8).…”
Section: Skin Cancermentioning
confidence: 88%
“…They develop antibodies of the IgE-type. Patients who have multiple squamous cell carcinomas have these antibodies more often (odds ratio 3.82 [95% CI 1.05-13.88]) [15]. This suggests that patients with an impaired epidermal barrier, which is indicated by the presence of sensitisation to common allergens, are at higher risk of developing non-melanoma skin cancer.…”
Section: Epidermal Barrier Dysfunction and Skin Cancermentioning
confidence: 99%